Students’ Perception toward the Use of Google Classroom as Teaching and Learning English Media for EFL Students - Gede Weda Rukmana (English Education Department STKIP Agama Hindu Singaraja, 2021)
This study aimed to investigate students’ perception toward the use of google classroom as a media for teaching language. This study is a library study. This study was focused on collecting information about the definition of Google Classroom, students’ perception toward the use of google classroom, and the performance of google classroom in language learning. Google classroom is one of the platforms that used to provide the material, task, information about the course to the students that given by the teacher by online. Google classroom help the students and also the teacher to make the learning process easier during the Covid-19 pandemic. Google Classroom gave students and teacher chance to keep doing the course during the Covid-19 pandemic. Therefore, this platform gets positive responses from many students. Most students were agreed that google classroom easy to be used and have good performance since it helps the students to save the file or the material that given by the teacher through google classroom easily, and also students can easily submit their work in this platform. By using Google Classroom, the teacher could do many things, such as assigned quiz to the students, gave the students video for additional source of the study, the teacher also could link many applications such as Quizizz, Google Form, Google Drive, and many more.